DNA Barcode of Barred Mudskipper (Periophthalmus argentilineatus Valenciennes, 1837) from Tekolok Estuary (West Nusa Tenggara, Indonesia) and Their Phylogenetic Relationship with Other Indonesian Barred Mudskippers - Febrina Amaliya Rha'ifa; Deiandra Jasmine Audrea; Lukman Hakim; Tuty Arisuryanti (Journal of Tropical Biodiversity and Biotechnology, 2021)
Barred mudskipper (Periophthalmus argentilineatus) has a potency to be developed as protein for human consumption and ornamental fish. The fish also has an important role in mangrove ecosystems. Nevertheless, many barred mudskippers have been considered a cryptic species. Therefore, accurate identification is needed to clarify species identification of the barred mudskipper using DNA barcoding.  This research aimed to identify barred mudskippers from Tekolok Estuary (East Lombok, West Nusa Tenggara, Indonesia) using COI mitochondrial gene as a DNA barcode and analyze genetic relationship with other barred mudskippers from several regions of Indonesia recorded in GenBank. This study used a PCR method with universal primers FishF2 and FishR2.  The data was then analysed using DNASTAR, BLAST, Mesquite, MEGA, DnaSP, BEAST, GenAlEx, and NETWORK. The results revealed that barred mudskipper from Tekolok Estuary has been verified as Periophthalmus argentilineatus. The results also exhibited that P. argentilineatus from Tekolok Estuary has a close genetic relationship to P.argentilineatus from Tukad Bilukpoh (Jembrana, Bali).  In addition, phylogenetic analysis showed that P.argentilineatus from Indonesia consisted of two clades with a genetic distance of approximately 6.64%. This analysis revealed evidence of the cryptic diversity of P.argentilineatus from Indonesia. Further detailed studies are needed to clarify whether Indonesian P.argentilineatus should be categorized into more than one species or single species with several subspecies.